Gender equality in Islamic education: a comparative study of the thought of Ki Hajar Dewantara and the thought of KH. Ahmad Dahlan - Ahmad Faroch Alfarizi; Arif Rahman (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Gender equality in Islamic education remains a significant discourse, especially when viewed through the perspectives of influential figures such as Ki Hajar Dewantara and KH. Ahmad Dahlan. This study aims to compare their thoughts on gender equality in education and analyze their relevance in the modern context. Using a qualitative approach with a comparative analysis method, this research examines primary sources, including writings, speeches, and educational practices. The results indicate that both figures emphasized inclusive education, yet their approaches differed: Ki Hajar Dewantara focused on humanist and nationalistic education, while KH. Ahmad Dahlan integrated religious values to promote gender equality. Ki Hajar Dewantara advocated equal educational access for all, emphasizing character development and independent thinking. Meanwhile, KH. Ahmad Dahlan emphasized the role of Islamic teachings in fostering balanced roles for men and women in society. The study concludes that their educational philosophies provide valuable insights for developing an inclusive and egalitarian Islamic education system today.